“Turning pumpkins into carriages”: sustainable urban development and the financialization of ‘green’ commercial real estate in France - Katia Attuyer; Antoine Guironnet; Ludovic Halbert (Articulo: Journal of Urban Research, 2012)
There is increasing pressure from political circles and citizens’ groups to ensure the production of urban built forms that can address both social and economic needs while respecting long-term environmental goals. This has resulted in new legislative and policy frameworks aimed at encouraging the adoption of sustainable development practices. This paper analyzes how professionals investing finance capital in commercial real estate properties in France are responding to such pressure. It raises the theoretical question of how sustainability goals may be internalized by investors in a context of financialization of urban production. Based on a qualitative analysis, the paper questions how property investors engage with the sustainability agenda and how this affects their organizational charts, business strategies, investment processes and day-to-day management of commercial real estate. The results show that FCIs have to internalize potentially contradictory objectives, i.e., countering the capital depreciation arising from new legislation by upgrading their portfolios and, at the same time, limiting their investments to maintain their profit margins. To achieve this, they both encourage their tenants to reduce energy consumption and adopt spatially selective ‘green’ investments that favor a limited number of ‘established’ markets at both intra and inter-urban levels.